Warm water pathways toward Nioghalvfjerdsfjorden Glacier, Northeast Greenland. Issue 5 (15th May 2017) - Schaffer, Janin; von Appen, Wilken‐Jon; Dodd, Paul A.; Hofstede, Coen; Mayer, Christoph; de Steur, Laura; Kanzow, Torsten
Abstract: Nioghalvfjerdsfjorden Glacier (79NG) is the largest of three marine‐terminating outlet glaciers draining the Northeast Greenland Ice Stream. To understand how Atlantic waters supply waters in the cavity beneath the floating 79NG, we analyze historic and recent bathymetric, hydrographic, and velocity observations obtained on the Northeast Greenland continental shelf. The bathymetry is characterized by a trough system, consisting of the Westwind Trough and the Norske Trough in the northern and southern part of the continental shelf, respectively. Atlantic waters recirculating in Fram Strait cross the shelf break and enter the trough system at its southeastern inlet toward the inner shelf. Warm Atlantic Intermediate Water (AIW) present below 200 m in the Norske Trough shows large contributions of the recirculating Atlantic water. We found that the bathymetry is sufficiently deep to provide a direct subsurface pathway for warm AIW between the shelf break and the 79NG cavity via the Norske Trough. Likewise, based on the hydrographic data, we show that the Norske Trough supplies AIW warmer than 1°C to the 79NG, which is not present in the Westwind Trough. Our moored and lowered velocity measurements indicate that a boundary current carries warm AIW along the northeastern slope of Norske Trough toward the 79NG. We suggest that anomalies in Atlantic water temperatures in Fram Strait could reach 79NG within less than 1.5 years, thereby modifying the glacier's basal melt rates. Key Points: The shelf bathymetry is sufficiently deep to provide a pathway for Atlantic waters toward the 79NG Warmest waters exceeding 1°C found at the bottom of the 79NG cavity originate from the Norske Trough A boundary current carries warm waters via Norske Trough toward the 79NG